Effects of Calcination Temperatures on The Catalytic Activities of Alumina Supported Cobalt and Chromium Catalysts - Mardwita Mardwita; Eka Sri Yusmartini; Nidya Wisudawati (Bulletin of Chemical Reaction Engineering & Catalysis, 2019)
Catalysts properties are important for catalytic reactions. The interaction between support and metal in a catalyst is resulted from catalyst preparation. In this study, gamma-alumina (Al2O3) supported cobalt (Co) and chromium (Cr) catalysts were prepared by impregnation method and calcined at two different temperatures, they are 400 °C for 4 hours and 800 °C for 4 hours. The resulted catalysts contained 10 wt.% of metal and denoted as Co/Al2O3(400), Co/Al2O33(800), Cr/Al2O3(400), and Cr/Al2O3(800) catalysts. The surface and state of the catalysts were examined by using x-ray diffraction (XRD), x-ray photoelectron spectrometer (XPS) and transmission electron microscopy (TEM). The XRD result reveals that strong interaction between Co and Al2O3 due to a formation of higher cobalt oxide. The XRD result further indicates aggregation and strong support metal interaction between Co and Al2O3 during calcination. On the other hand, TEM result showed that large Co particle was observed on Al2O3. The Cr/Al2O3 catalysts were characterized by using XPS. The XPS results showed that Cr/Al2O3(800) catalyst was dominated by Cr6+ species at binding energy 579.04 eV, indicating high dispersion of Cr on Al2O3. Moreover, Cr metal particle was not observed on XRD and TEM image. All the characterization results provide information that the impregnated metal on Al2O3 showed different properties. Co metal particle tends to be more oxidized and formed large particle, however it was not observed on Cr metal particle.